An overview of the irreversible electroporation for the treatment of liver metastases: When to use it - Belfiore, Maria Paola; De Chiara, Marco; Reginelli, Alfonso; Clemente, Alfredo; Urraro, Fabrizio; Grassi, Roberto; Belfiore, Giuseppe; Cappabianca, Salvatore (Frontiers in Oncology, 2022)
Tumour ablation is an established therapy for local treatment of liver metastases and hepatocellular carcinoma. Most commonly two different kind of thermic ablation, radiofrequency ablation and microwave ablation, are used in clinical practice. The aim of both is to induce thermic damage to the malignant cells in order to obtain coagulative necrosis of the neoplastic lesions. Our main concerns about these procedures are the collateral thermic damage to adjacent structures and heat-sink effect. Irreversible electroporation (IRE) is a recently developed, non-thermal ablation procedure which works applying short pulses of direct current that generate an electric field in the lesion area. The electric field increase the transmembrane potential, changing its permeability to ions.Irreversible electroporation does not generate heat, giving the chance to avoid the heat-sink effect and opening the path to a better treatment of all the lesions located in close proximity to big vessels and bile ducts. Electric fields produced by the IRE may affect endothelial cells and cholangiocytes but they spare the collagen matrix, preserving re-epithelization process as well as the function of the damaged structures. Purpose of the authors is to identify the different scenarios where CT-guided percutaneous IRE of the liver should be preferred to other ablative techniques and why.